Toward High‐Performance Photodetectors Based on Quasi‐2D Ruddlesden‐Popper Mixed‐n Perovskite Nanomaterials - Christian Klinke (Advanced Functional Materials, 2025)
The excellent optoelectronic properties, straightforward synthesis, and robust material stability of quasi‐2D metal halide perovskites have made them a hot research topic for optoelectronic devices. In layered organic–inorganic perovskites, the optoelectronic properties are greatly influenced by morphology and quantum confinement, which are crucial for their photodetection performance and offer an excellent tunability tool. Here the optoelectronic properties and photodetection performance of quasi‐2D methylammonium lead bromide perovskites with three different morphologies nanoplatelets, nanosheets, and nanostripes produced by colloidal hot injection technique are investigated. The structural and optical characterization reveals the mixed‐n phases with varying extents of confinement. The study shows that nanostripes with the weak confinement effect exhibit superior photodetection performance. They demonstrate the highest photoresponsivity (R), external quantum efficiency (EQE), and detectivity (D) of 183 mA W−1, 56% and 2.9 × 1011 Jones respectively. They also show the highest on/off ratio and fastest photoresponse (rise time (τ r ) = 3.4 and fall time (τ f ) = 4.3 ms) in comparison to nanoplatelets and nanosheets. The study will aid in realizing an inexpensive high‐performance photodetector based on nanoparticles of quasi‐2D perovskites.